Safety profiles of cyclosporine and tacrolimus in pregnancy: a pharmacovigilance analysis using the FDA Adverse Event Reporting System - Yanhong Deng; Senling Feng; Shengying Shi; Zhongwen Yuan; Zhengrong Mei; Jinjin Yin; Dongdong Jing; Shaozhi Liu (Frontiers in Medicine, 2026)
Background The increasing use of calcineurin inhibitors (CNIs) among pregnant women highlights the importance of continuous safety surveillance. This study aimed to characterize the real-world safety signals of cyclosporine (CsA) and tacrolimus (TAC) during pregnancy using data from the FDA Adverse Event Reporting System (FAERS) database. Methods We applied four disproportionality data-mining algorithms (reporting odds ratio, proportional reporting ratio, Bayesian confidence propagation neural network, and empirical Bayesian geometric mean) and performed sensitivity analyses restricted to monotherapy cases to minimize confounding by concomitant medications. Results A total of 761 CsA-associated and 2,204 TAC-associated pregnancy cases were identified in the FAERS database. Disproportionality analyses yielded 80 positive signals for CsA and 116 for TAC. Both drugs shared signals for common AEs, such as low birth weight, preterm birth, fetal growth restriction, gestational hypertension, and preeclampsia, as well as signals consistent with known nephrotoxicity and neurotoxicity. Comparative signal detection showed that CsA signals were predominantly associated with kidney transplant rejection and elevated creatinine, whereas TAC signals were predominantly associated with thrombotic microangiopathy. Conclusion This pharmacovigilance study demonstrates that CsA and TAC share overlapping AE signal profiles during pregnancy, especially for maternal/fetal complications, nephrotoxicity, and neurotoxicity, yet they also exhibit divergent signals that may reflect differences in their safety profiles. Given the exploratory nature of disproportionality analysis, confirmation through prospective clinical studies is warranted.